Environmental Impact Analysis of Biogas Production Using Life Cycle Assessment (LCA) Towards Net Zero Emissions - Aulia Putri Fatiha; Muniroh Muniroh; Shofa Aulia Aldhama (Transpublika Publisher, 2025)
The dairy cattle sector in Indonesia significantly contributes to greenhouse gas (GHG) emissions, particularly methane (CH₄). This study aims to analyze the environmental impacts of biogas production using the Life Cycle Assessment (LCA) approach. Data was collected from several biogas projects in Central Java and Yogyakarta, then analysed using OpenLCA software with cradle-to-grave system boundaries. The analysis was conducted using the Life Cycle Assessment (LCA) approach to assess the environmental impact at each stage of the life cycle, from raw material collection and production processes to utilisation and final disposal. In addition, supporting data was collected through interviews with project managers, field observations, and literature studies to ensure the accuracy and completeness of the analysis results. The results indicate that anaerobic digestion and biogas combustion are the major contributors to emissions but also play a key role in reducing methane release by up to 60%. Optimization of digester management and utilization of digestate as organic fertilizer can further minimize additional impacts. Hence, biogas demonstrates substantial potential as a mitigation strategy to support net zero emissions in the dairy cattle sector.